Studi Wacana Kritis, Pengajaran Bahasa Indonesia, dan Perspektif Emansipasi - Santoso, Anang (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
The characteristics of language use in the global era include language instability, the prominence of language hybridity, discourse commodification, and technologized discourse. Language has demonstrated its role as a determining factor in hegemony, a phenomenon that Indonesian language teachers should take into consideration. Therefore, the teaching of the Indonesian language should be developed based on the principles of critical discourse analysis. Consequently, learners of Indonesian should develop critical language awareness and language sensitivity from the perspective of emancipation.